Noninvasive assessment and risk factors of liver fibrosis in patients with thalassemia major using shear wave elastography. Issue 1 (1st January 2019) - Al-Khabori, Murtadha; Daar, Shahina; Al-Busafi, Said A.; Al-Dhuhli, Humoud; Alumairi, AlGhalya A.; Hassan, Moez; Al-Rahbi, Sara; Al-Ajmi, Umaima
ABSTRACT: Objectives : This study aimed to estimate the prevalence of liver fibrosis and assess the risk factors for developing significant liver fibrosis in patients with Thalassemia Major (TM). Methods: All patients with TM over the age of 10 years were included in the study. Results: A total of 94 eligible patients underwent 2-D SWE. The median age was 26.7 years. The median of the average 5-year serum ferritin (5yrSF) and liver iron concentration (LIC) assessed by MRI T2* were 1326 µg/L and 6.7 mg/g dw, respectively. Hepatitis C and hepatitis B core antibodies were positive in 38% and 1% of the patients respectively. The proportion of patients with significant fibrosis was 60%. Male gender increased the risk of significant fibrosis (Odds ratio of 0.4; p = .0373). Additionally, the 5yrSF ( p = .00661), the LIC ( p = .0225) and the lowest LIC of the previous 5 years ( p = .0211) were significant. In the multivariable logistic regression model, only 5yrSF ( p = .0035) and gender ( p = .00984) remained significant. Conclusions: The risk of liver fibrosis is associated with iron overload and gender in patients with TM.